MEDICATION ERROR OVERVIEW AND PREVENTION STRATEGIES - Khan, Ahmad (American International Journal of Social Science Research, 2021)
This literature review aims to highlight the overview of medication errors and strategies to avoid and decrease medication errors. Availability of various types of over-the-counter and prescribed medication has added to the risk of medication. Also, the medication chain has different steps, and different people are involved in each step, such as prescribing medication, dispensing, and administering medication. Every phase in the medication chain is prone to risks that can lead to medication errors. Medication safety is the responsibility of every healthcare professional involved in the medication chain to deliver effective and safe care to patients with an optimal outcome. A medication error can happen in every health care setting to decrease and prevent medication errors. It is critically important to have complete knowledge of the medication use chain and integrate evidence-based strategies, such as medication reconciliation, analysis of medication error, double-check, and avoiding interruption and distraction into practice. Medication errors can lead to patient harm, prevent on-time discharges, and increase care costs. Medication safety culture can shine in a setting of effectively applying strategy into practice, and everyone's collaboration and commitment to adhere to medication safety strategy can improve patient safety.